Chemical Composition of Juniperus communis L. Cone Essential Oil and Its Variability among Wild Populations in Kosovo. Issue 11 (November 2015) - Hajdari, Avni; Mustafa, Behxhet; Nebija, Dashnor; Miftari, Elheme; Quave, Cassandra L.; Novak, Johannes
Abstract: Ripe cones of Juniperus communis L. (Cupressaceae) were collected from five wild populations in Kosovo, with the aim of investigating the chemical composition and natural variation of essential oils between and within wild populations. Ripe cones were collected, air dried, crushed, and the essential oils obtained by hydrodistillation. The essential‐oil constituents were identified by GC‐FID and GC/MS analyses. The yield of essential oil differed depending on the population origins and ranged from 0.4 to 3.8% ( v / w, based on the dry weight). In total, 42 compounds were identified in the essential oils of all populations. The principal components of the cone‐essential oils were α ‐pinene, followed by β ‐myrcene, sabinene, andD ‐limonene. Taking into consideration the yield and chemical composition, the essential oil originating from various collection sites in Kosovo fulfilled the minimum requirements for J. communis essential oils of the European Pharmacopoeia. Hierarchical cluster analysis (HCA) and principal component analysis (PCA) were used to determine the influence of the geographical variations on the essential‐oil composition. These statistical analyses suggested that the clustering of populations was not related to their geographic location, but rather appeared to be linked to local selective forces acting on the chemotype diversity. Abstract :